TRAINING ON FLOURISHING SPEAKING CLASS THROUGH SHORT STORIES IN MADRASAH ALIYAH NEGERI 1 PROBOLINGGO - Tirmidi, Tirmidi; Putri, Faradila Arsylia; Khomariyah, Yanti; Indriyani, Kholifatul (Community Development Journal : Jurnal Pengabdian Masyarakat, 2024)
To help the students to master English, Madrasah Aliyah Negeri 1 Probolinggo provides additional activities named English Study Club. On tutors’ guidance, the activities range from reading to speaking. In the initial observations made by the practitioners, it was found that the study club has not yet had a learning activity plan for each meeting, for both reading, nor speaking. It was also found that participants in the club were less enthusiastic in joining speaking activities class. This happened because they were lack of ideas to convey in the speaking session. This community service aims to provide training to tutors at the study club so that they can create an enthusiastic class. The activities in question are reading activities through mastering stories in short stories which can then be used as topics in discussion activities in speaking class. For this reason, this service focuses on training tutors to prepare reading comprehension learning activities using short stories as pre-activities in speaking classes. The expected outcome is that the tutors can overcome the boredom experienced by the English study club participants. Gladly, this aim is on its path of materialization.